1998
DOI: 10.1080/10473289.1998.10463725
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Quantity of Heavy Metal and PAHs in Fly Ash

Abstract: Heavy metal and polycyclic aromatic hydrocarbons (PAHs) in flue gas have received considerable attention in recent years due to their mutagenic or carcinogenic properties. The present study is carried out to investigate the influence of the quantity of heavy metals on PAHs formation in fly ash. A fluidized bed incinerator was used in this experiment to obtain fly ash of chemical similarity by incinerating various compositions of waste. The obtained fly ash, both with and without heavy metal, were used to adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 4 publications
0
11
1
Order By: Relevance
“…Rose and Juggins 1994;Fernandez et al 2002). Despite their size (typically 2 − 20 μm), their presence has been recorded in the sediments of many remote lakes in both northern and southern hemispheres (e.g., Bindler et al, 2001;Rose et al 2004; where they have proved useful in identifying anthropogenic influences while their large, and frequently porous, surface areas result in them being considered an important means by which toxic pollutants such as trace metals and persistent organic pollutants (Ghosh et al 2000;Wey et al 1998) may be atmospherically transported and deposited.…”
Section: Rationale For This Studymentioning
confidence: 99%
“…Rose and Juggins 1994;Fernandez et al 2002). Despite their size (typically 2 − 20 μm), their presence has been recorded in the sediments of many remote lakes in both northern and southern hemispheres (e.g., Bindler et al, 2001;Rose et al 2004; where they have proved useful in identifying anthropogenic influences while their large, and frequently porous, surface areas result in them being considered an important means by which toxic pollutants such as trace metals and persistent organic pollutants (Ghosh et al 2000;Wey et al 1998) may be atmospherically transported and deposited.…”
Section: Rationale For This Studymentioning
confidence: 99%
“…Petersen et al, 1995;Seigneur et al, 2005) and POPs (e.g. Ohsaki et al, 1995;Wey et al, 1998;Ghosh et al, 2000;Persson et al, 2005) are known to bind to their surfaces and hence the erosive transfer of these particulate contaminants may further enhance metal and POPs inputs from soils to surface waters.…”
Section: Implications Of Climate Changementioning
confidence: 99%
“…flowmeter, (7) thermocouple, (8) pressure detector, (9) preheater chamber, (10) sand bed, (11) electric resistance, (12) U manometer, (13) cyclone, (14) induced fan, (15) secondary fluidized bed.…”
Section: Compoundsmentioning
confidence: 99%
“…Addition of Al 2 O 3 mixed with bed materials may lead a reducing of fluidized bed quality. Wey et al [13] showed the combustion efficiency of fluidized bed incinerator was influenced by adding CaO. Lin et al [14] indicated the fluidized behavior of a bimodal particle size tend to segregate and reduce combustion efficiency.…”
Section: Effect Of Different Aditives Mixed With Bed Materialsmentioning
confidence: 99%